2021
DOI: 10.3390/ijms22083985
|View full text |Cite
|
Sign up to set email alerts
|

DCTN1 Binds to TDP-43 and Regulates TDP-43 Aggregation

Abstract: A common pathological hallmark of several neurodegenerative diseases, including amyotrophic lateral sclerosis, is cytoplasmic mislocalization and aggregation of nuclear RNA-binding protein TDP-43. Perry disease, which displays inherited atypical parkinsonism, is a type of TDP-43 proteinopathy. The causative gene DCTN1 encodes the largest subunit of the dynactin complex. Dynactin associates with the microtubule-based motor cytoplasmic dynein and is required for dynein-mediated long-distance retrograde transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Further studies will be needed to determine whether differences in the motility of TDP-43 WT and mutant RNP granules can be explained by loss of direct and/or indirect association with the motor proteins kinesin 1 and dynein ( Chu et al, 2019 ). Recently, it was shown that TDP-43 interacts with dynactin and regulates retrograde transport in a cell line ( Deshimaru et al, 2021 ). Therefore, it will be important to understand whether different ALS-linked mutants and TDP-43 substitutions are able to associate with dynactin and other adaptor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be needed to determine whether differences in the motility of TDP-43 WT and mutant RNP granules can be explained by loss of direct and/or indirect association with the motor proteins kinesin 1 and dynein ( Chu et al, 2019 ). Recently, it was shown that TDP-43 interacts with dynactin and regulates retrograde transport in a cell line ( Deshimaru et al, 2021 ). Therefore, it will be important to understand whether different ALS-linked mutants and TDP-43 substitutions are able to associate with dynactin and other adaptor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the latter shows some clinical and pathological similarities with those related to the DNAJB2 phenotype. It is characterized clinically by early‐onset parkinsonism, depression/apathy and central hypoventilation, and pathologically by degeneration of dopaminergic neurons and TDP‐43 proteinopathy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Such mutation produces a G59S substitution in DCTN1 CAP-Gly domain that alters the folding of DCTN1 microtubule-binding domain, reducing the affinity of the mutant protein for microtubules. G59S DCTN1 tends to misfold and form neurotoxic aggregates that were shown to sequester dynein, mitochondria, and TDP-43 (Puls et al 2003 , 2005 ; Levy et al 2006 ; Deshimaru et al 2021 ). Additional DCTN1 mutations lying both in DCTN1 CAP-Gly domain and in its dynein-binding domain have then been identified in ALS (Münch et al 2004 ; Stockmann et al 2013 ; Liu et al 2014 , 2017 ), including those forms with an FTD component (Münch et al 2005 ).…”
Section: Autophagic Genes Involved In Alsmentioning
confidence: 99%